Semantic Web Technologies in Healthcare: A Scoping Review - Miranda, Nelson; Machado, Matheus Matos; Moreira, Dilvan A. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
This scoping review explores the application of Semantic Web technologies in healthcare, focusing on enhancing Electronic Health Records (EHRs). The review synthesizes research from various databases, identifying the role and impact of technologies such as RDF, OWL, and SPARQL in improving data interoperability and management within healthcare systems. Through a systematic classification and analysis of the literature, significant advancements and existing gaps in current research are highlighted. The findings suggest that while Semantic Web technologies have facilitated substantial improvements in data handling and system interoperability, challenges remain in full integration across diverse health information systems. This review underscores the potential of these technologies to transform healthcare practices by enabling more effective data integration, discovery, and management.